Rehabilitation of Mangrove Ecosystem Through Community-Based Project and the Current Economic Value: A Case Study of Rehabilitation Project in Lubuk Kertang Village, Langkat Regency, North Sumatera - Natasha Dinda; Suadi Suadi; Latif Sahubawa (Universitas Gadjah Mada, 2018)
Mangrove ecosystem plays an important role for socio-economic and environmental services. However, the rapid expansion of agricultural and industrial plantation activities challenged the sustainability of such ecosystem in Lubuk Kertang Village. This research aims to describe the potential of community-based to rehabilitate the degraded mangrove ecosystem and the economic benefit of such project for Lubuk Kertang villagers. The research was conducted using census methods for all respondents, including fishermen, handicraft makers, tourists, and the manager of the eco-tourism activity. The study showed that the successful of community on replanting the mangrove on mangrove ecosystem led by various factors, including the high willingness of community to participate on rehabilitation project, clear physical boundaries and rule enforcement, effective monitoring system and better conflict resolution mechanism. The total economic value in the mangrove area is Rp 1.057.343.654/year, comprising of Rp 601.077.437/year direct use value, Rp 395.786.267/year indirect value, Rp 22.279.950/year option use value, and Rp 38.200.000 existence value. The society based mangrove management has preserved the benefit potential value of not to endanger the change of mangrove ecosystem.